2018
DOI: 10.1590/1980-5373-mr-2018-0502
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dilution on the Microstructure and Properties of CoCrMoSi alloy Coatings Processed on High-Carbon Substrate

Abstract: The Laves phase reinforced CoCrMoSi alloy system has emerged as a candidate material to protect the surface of components to withstand harsh environments under wear and/or corrosion. However, previous reports have raised some concerns and restricted a wider selection of iron-based substrates to be coated, especially limiting the carbon content. This work aims to outline the Laves -Carbides phases in the microstructure and its effect on the properties of T400 alloy deposited on GGG40 ductile iron. Dilution of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
(40 reference statements)
1
7
0
Order By: Relevance
“…Some authors observed a significant increase in the mechanical properties of the coatings (e.g. hardness and wear resistance) when a carbide former-containing alloy is deposited on a high-carbon content substrate [3][4][5] . Otherwise, high dilution processing on low carbon substrates usually induces a drop in mechanical properties 3,6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Some authors observed a significant increase in the mechanical properties of the coatings (e.g. hardness and wear resistance) when a carbide former-containing alloy is deposited on a high-carbon content substrate [3][4][5] . Otherwise, high dilution processing on low carbon substrates usually induces a drop in mechanical properties 3,6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…A solution for extending the lifespan of components which operate in corrosive environments with high-wear loads could be protective resistant coatings on high-temperature resistant stainless steels and superalloys. Usually, stainless steels are coated with superalloys for greater strength [2,[4][5][6]. Depositing coatings is a smarter and less expensive way of meeting the industrial design requirements for such materials [6].…”
Section: Introductionmentioning
confidence: 99%
“…Usually, stainless steels are coated with superalloys for greater strength [2,[4][5][6]. Depositing coatings is a smarter and less expensive way of meeting the industrial design requirements for such materials [6].…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, the deposition onto high-carbon substrates may lead to a significant increase in the coatings wear resistance 13,14 . Therefore, some works revealed the possibility of coating design by cladding with substrate material selection and dilution control [12][13][14][15][16][17][18] while many others indicated, as a research opportunity, the processing of composite coatings by laser cladding [2][3][4][5][6][7][8][9][10] . The latter involves an even more intricate task because of the need to select and manage the clad alloy, reinforcement particle type, and its amount, substrate, and laser processing parameters 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Figure16. Interdendritic carbides formed in the coatings deposited with 3.0 kW laser power and 30% NbC feeding rate.…”
mentioning
confidence: 99%